Prevalence of hypertension and its risk factors among urban school children of Belagavi- a cross sectional study - Gunagi, Praveena; Harikanth, Disha Rama; Mulsange , Kailas (International Journal Of Community Medicine And Public Health, 2023)
Background: Primary hypertension is becoming common among apparently healthy children. Measures for early diagnosis of pre hypertension and hypertension along with its risk factors during childhood could benefit from earlier intervention and follow-up. Methods: This cross sectional study was conducted among 270 urban school students of Belagavi of class 10th in 2016 by using a structured questionnaire followed by anthropometry and blood pressure measurement. Results: About 39% of children had family history of hypertension and 27% had family history of chronic diseases. Majority had inadequate consumption of vegetables (84.07%) and fruits (83.70%). The overall physical activity among the students was inadequate (78.15%) and about 46.30% of them got easily angered, stressed or irritated. The waist circumference of 14.07% students was falling in obese category. About 11.48% of them were overweight and 7.04% were obese according to their body mass index. Among the students, 71.85% had normal blood pressure and 18.15% had pre-hypertension. Hypertension was detected among 10.00% of students of which 5.56% belonged to stage I and 4.44% belonged to stage II hypertension. Statistical association between the blood pressures of school children showed significance with family history of chronic diseases (p=0.025), body mass index and waist circumference (p<0.001). Conclusions: One tenth of the children had hypertension and one fifth of the children had pre-hypertension. The children who were obese had increased blood pressure than those with normal weight. Health promotion at early phase of life can help in the prevention of hypertension.